2021
DOI: 10.3390/molecules26247708
|View full text |Cite
|
Sign up to set email alerts
|

Aquilaria Species (Thymelaeaceae) Distribution, Volatile and Non-Volatile Phytochemicals, Pharmacological Uses, Agarwood Grading System, and Induction Methods

Abstract: Agarwood is a highly valuable fragrant wood of Aquilaria spp. (Thymelaeaceae) which has been widely utilized in traditional medicine, religious rites, and cultural activities. This study summarizes a review on the identification of Aquilaria cultivars, volatile and non-volatile phytochemicals, pharmacological uses, and agarwood grading system to determine its quality, and different agarwood induction methods. Due to the highly demanding and depleted natural resources, the research on agarwood is still insuffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…The results showed that agarwood volatile oil has a versatile sedative and hypnotic effect, and its mechanism of action may be related to regulating the gene expression of GABAA receptor, enhancing the function of GABAA receptor, and promoting the influx of CL -1 [30]. Researches have compared the analgesic effects of different years of agallodendron, and deduce that the volatile oil of agallodendron can significantly increase the pain threshold of mice and reduce the number of writhing induced by acetic acid in mice, proving that it has a clear analgesic effect [31]. The nonsteroidal anti-inflammatory drug diclofenac is a commonly used anti-inflammatory drug with analgesic and anti-inflammatory effects.…”
Section: Analgesic and Sedative Effectsmentioning
confidence: 99%
“…The results showed that agarwood volatile oil has a versatile sedative and hypnotic effect, and its mechanism of action may be related to regulating the gene expression of GABAA receptor, enhancing the function of GABAA receptor, and promoting the influx of CL -1 [30]. Researches have compared the analgesic effects of different years of agallodendron, and deduce that the volatile oil of agallodendron can significantly increase the pain threshold of mice and reduce the number of writhing induced by acetic acid in mice, proving that it has a clear analgesic effect [31]. The nonsteroidal anti-inflammatory drug diclofenac is a commonly used anti-inflammatory drug with analgesic and anti-inflammatory effects.…”
Section: Analgesic and Sedative Effectsmentioning
confidence: 99%
“…1 This plant is the source of the fragrant product 'agarwood', which plays important roles in traditional medicines, religious ceremonies, and incense industries. 2 Agarwood with high quality can sell for up to 30 000 US dollars per kilogram in the international market and therefore has been considered as 'one of the most expensive natural ingredients in the world'. 3 Due to illegal logging, the wild population of A. sinensis sharply decreased and has been listed as the national secondclass protected wild plant in China.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Although it has garnered widespread acclaim, the scarcity of agarwood resulting from natural calamities and anthropogenic factors has caused a decline in wild populations, leading to a shortage of agarwood and an inflated market price. [7][8][9] Agarwood originates from diverse and distinct regions, although Guan-xiang, Hoi-an, and Sin-chew zones are three main production areas. The quality and chemical composition of agarwood are influenced by its specific place of origin, [10][11][12] and its multifaceted origins coupled with scarcity and escalating market demand have presented challenges in maintaining consistent quality control measures for this precious material.…”
mentioning
confidence: 99%
“…5,6 Although it has garnered widespread acclaim, the scarcity of agarwood resulting from natural calamities and anthropogenic factors has caused a decline in wild populations, leading to a shortage of agarwood and an inflated market price. 7–9…”
mentioning
confidence: 99%